A numerical method for solving the Oseen-type problem in an L-shaped domain - Rukavishnikov, A.V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2018)
In this paper we introduce the notion of an Rν-generalized solution to the Oseen-type problem in rotation form in a polygonal domain with a reentrant obtuse angle on its boundary. We propose a weighted finite element method to solve this problem approximately. A number of numerical experiments performed on a model problem in an L-shaped domain show the advantages of the proposed method.